1997
DOI: 10.1086/515470
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of a Gene Causing High Bone Mass to Human Chromosome 11 (11q12-13)

Abstract: The purpose of this paper is to report the linkage of a genetic locus (designated "HBM") in the human genome to a phenotype of very high spinal bone density, using a single extended pedigree. We measured spinal bone-mineral density, spinal Z(BMD), and collected blood from 22 members of this kindred. DNA was genotyped on an Applied Biosystems model 377 (ABI PRISM Linkage Mapping Sets; Perkin Elmer Applied Biosystems), by use of fluorescence-based marker sets that included 345 markers. Both two-point and multipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
198
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(208 citation statements)
references
References 30 publications
6
198
0
4
Order By: Relevance
“…Two groups have previously reported lod scores suggestive of linkage of bone density to chromosome 11q 20,21 with a maximum at the locus D11S987. This marker is located near the centromere, probably within 11q12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups have previously reported lod scores suggestive of linkage of bone density to chromosome 11q 20,21 with a maximum at the locus D11S987. This marker is located near the centromere, probably within 11q12.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Linkage and association studies have suggested that some other genes that condition BMD are the vitamin D receptor (see 18 for review) and the estrogen receptor. 19 Linkage studies in two disorders, osteoporosis-pseudoglioma syndrome 20 and a high bone mass trait 21 indicate that a gene or genes on chromosome 11q can influence bone density.…”
Section: Introductionmentioning
confidence: 99%
“…The embryonic expression pattern of Wnt11, particularly its restricted expression to the perichondrium of the developing skeleton, has long suggested its role in skeletal development 138. Interestingly, the chromosomal location of Wnt11 to 11q13.5 is near previously linked markers of high bone mass 138, 139. In addition, Wnt11 expression is upregulated during mesenchymal osteogenesis 140.…”
Section: Implication Of Noncanonical Wnt Signaling In Vcmentioning
confidence: 99%
“…The LRP5 pathway was discovered to be a key regulator of bone mass following linkage studies in two rare human diseases: OPPS, which is a recessively inherited condition characterized by severe, early onset osteoporosis and congenital blindness due to vitreous opacity (Gong et al 1998), and the HBM syndrome that is an asymptomatic autosomal dominant disorder characterized by increased bone mineral density (Johnson et al 1997). Both of these conditions were mapped to the same region of chromosome 11q12 in the late 1990s, and different mutations in the LRP5 gene were eventually identified as the cause of both disorders by positional cloning studies (Gong et al 2001;Little et al 2002).…”
Section: Lipoprotein Receptor-related Protein 5 (Lrp5)mentioning
confidence: 99%